2014
DOI: 10.1002/path.4471
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis airway epithelium remodelling: involvement of inflammation

Abstract: Chronic inflammation is a hallmark of cystic fibrosis (CF) lung disease and airway epithelium damage and remodelling are important components of lung pathology progression in CF. Whether this remodelling is secondary to deleterious infectious and inflammatory mediators, or to alterations of CF human airway epithelial (HAE) cells, such as their hyper inflammatory phenotype or their basic cystic fibrosis transmembrane conductance regulator (CFTR) default, remains debated. In this study, we evaluated the involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
5
45
0
4
Order By: Relevance
“…We first tested whether the treatment of healthy ALI-cultured human nasal epithelial cells (HNECs) with inflammatory cytokines, which models some of the changes that take place in the respiratory epithelium during chronic inflammation (3), will affect PCP acquisition. We found that healthy HNECs treated during differentiation with IL-1β, IL-13, or TNF-α, inflammatory cytokines commonly detected in CF epithelia (3638), have no or greatly decreased numbers of MCCs, and VANGL1 shows little or no asymmetry (Figures 4C and 2B for IL-13–treated MTECs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tested whether the treatment of healthy ALI-cultured human nasal epithelial cells (HNECs) with inflammatory cytokines, which models some of the changes that take place in the respiratory epithelium during chronic inflammation (3), will affect PCP acquisition. We found that healthy HNECs treated during differentiation with IL-1β, IL-13, or TNF-α, inflammatory cytokines commonly detected in CF epithelia (3638), have no or greatly decreased numbers of MCCs, and VANGL1 shows little or no asymmetry (Figures 4C and 2B for IL-13–treated MTECs).…”
Section: Resultsmentioning
confidence: 99%
“…These events contribute to severe, chronic inflammation and to cycles of repeated injury and imperfect repair. These in turn bring about epithelial dysfunction, which includes structural and functional changes such as hyperplasia of mucus-secreting cells, decrement in MCC numbers, abnormal tissue architecture with scarring, diminished barrier function, and decreased regenerative capacity (3). CF patients march down an inevitable slope of chronic cough, dyspnea, sinusitis, recurrent antibiotic and steroid use, and oxygen dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pathogen clearance facilitates infection that induces neutrophilic inflammation, leading to progressive epithelial damage within the conducting airways [16][17][18][19]. Over time, a recurrent cycle of intense inflammation, epithelial injury and airway remodeling produce irrevocable damage that dramatically compromises lung function [20][21][22]. Mounting evidence from in vitro studies and animal models of CF indicate that CFTR malfunction appears to alter the innate immune response of the airways leading to increased release of proinflammatory mediators evoking an amplified, yet less effective inflammatory reaction that is unable to eliminate airway pathogens [17,18].…”
Section: Airway Inflammation and Epithelial Damagementioning
confidence: 99%
“…This is particularly important since uncontrolled airway remodelling occurs in CF patients which is now recognized to start early in life and is linked to a poor pulmonary outcome with extensive fibrosis [27]. A similar process in CF patients also known to start in babyhood is the destruction of the pancreas which is driven by fibrosis and noted when the disease was first recognized.…”
Section: Control Cells C38 (With Transfected Add Back Truncated Functmentioning
confidence: 99%